Geographical variation and trends in outcomes of laparoscopic spleen-preserving distal pancreatectomy with or without splenic vessel preservation: A meta-analysis. (September 2017) - Yongfei, Hua; Javed, Ammar A.; Burkhart, Richard; Peters, Niek A.; Hasanain, Alina; Weiss, Matthew J.; Wolfgang, Christopher L.; He, Jin
Abstract: Background: Distal pancreatectomy (DP) is performed to treat tumors of the pancreatic body and tail. Traditionally, splenectomy is performed with a DP, however, laparoscopic spleen-preserving DP (SPDP) using Warshaw's (splenic vessels ligation) or Kimura's (splenic vessels preservation) techniques have been reported. The clinical benefits of using either technique remain unclear. In this study, we conducted a meta-analysis to compare the clinical outcomes of patients undergoing Warshaw's and Kimura SPDP. This is the first study to evaluate the geographical variation in outcomes of Warshaw's and Kimura SPDP. Methods: Databases of PubMed, Embase, and Cochrane library were used to identify studies reporting Warshaw's and Kimura SPDP. Clinical outcomes were compared. Pooled odds risk and weighted mean difference with 95% confidence interval were calculated using random effect models. Results: Fourteen non-randomized controlled studies involving 945 patients met our selection criteria. 301 (31.9%) patients underwent Warshaw's SPDP; 644 (68.1%) underwent Kimura SPDP. Compared to Warshaw's SPDP, patients undergoing Kimura SPDP had a lower incidence of post-operative complications including spleen infarction (OR = 9.64, 95% CI = 5.79 to 16.05, P < 0.001) and gastric varices (OR = 11.88, 95% CI = 5.11 to 27.66, P < 0.001). The length of surgery was significantly shorter for Warshaw's SPDP (WMD = −18.12, 95%CI = −26.52 to −9.72, p < 0.001). Decreased blood loss was reported for patients undergoing Warshaw's SPDP (WMD = −59.72, 95%CI = −102.01 to −17.43, p = 0.006). There were no differences between the two groups' rates of conversion to an open procedure (P = 0.35), postoperative pancreatic fistula (P = 0.71), need for reoperation (P = 0.25), and length of hospital stay (P = 0.38). Conclusion: Both Warshaw's and Kimura are safe SPDP techniques. These data suggest Kimura SPDP is the preferred technique due to less risk of splenic infarct and gastric varices. Despite evidence of regional variation in volume performed (between Kimura and Warshaw's), there are no statistically significant differences in outcomes between these techniques. Highlights: Both Warshaw and Kimura techniques for laparoscopic spleen-preserving distal pancreatectomy are safe but the clinical benefits of using either technique remain unclear. Compared to Kimura technique, Warshaw technique is quicker and has less blood loss but higher rates of splenic infarct and gastric varices. First study evaluating the geographical variations in outcomes of Warshaw and Kimura techniques. Despite evidence of regional variation in volumes and outcomes, these trends were not statistically significant.